Epidemiological and evolutionary dynamics of influenza B virus in coastal Kenya as revealed by genomic analysis of strains sampled over a single season. Issue 2 (16th August 2020) - Nyasimi, Festus M; Owuor, David Collins; Ngoi, Joyce M; Mwihuri, Alexander G; Otieno, Grieven P; Otieno, James R; Githinji, George; Nyiro, Joyce U; Nokes, David James; Agoti, Charles N
Abstract: The genomic epidemiology of influenza B virus (IBV) remains understudied in Africa despite significance to design of effective local and global control strategies. We undertook surveillance throughout 2016 in coastal Kenya, recruiting individuals presenting with acute respiratory illness at nine outpatient health facilities (any age) or admitted to the Kilifi County Hospital (<5 years old). Whole genomes were sequenced for a selected 111 positives; 94 (84.7%) of B/Victoria lineage and 17 (15.3%) of B/Yamagata lineage. Inter-lineage reassortment was detected in ten viruses; nine with B/Yamagata backbone but B/Victoria NA and NP segments and one with a B/Victoria backbone but B/Yamagata PB2, PB1, PA, and MP segments. Five phylogenomic clusters were identified among the sequenced viruses; (i), pure B/Victoria clade 1A ( n  = 93, 83.8%), (ii), reassortant B/Victoria clade 1A ( n  = 1, 0.9%), (iii), pure B/Yamagata clade 2 ( n  = 2, 1.8%), (iv), pure B/Yamagata clade 3 ( n  = 6, 5.4%), and (v), reassortant B/Yamagata clade 3 ( n  = 9, 8.1%). Using divergence dates and clustering patterns in the presence of global background sequences, we counted up to twenty-nine independent IBV strain introductions into the study area (∼900 km 2 ) in 2016. Local viruses, including the reassortant B/Yamagata strains, clustered closely with viruses from neighbouring Tanzania and Uganda. Our study demonstrated that genomic analysis provides a clearer picture of locally circulating IBV diversity. The high number of IBV introductions highlights the challenge in controlling local influenza epidemics by targeted approaches, for example, sub-population vaccination or patient quarantine. The finding of divergent IBV strains co-circulating within a single season emphasises why broad immunity vaccines are the most ideal for influenza control in Kenya.